IPv6 Security Issues: A Systematic Review Following PRISMA Guidelines - Shubair A. Abdullah; Ahmed A. Al Ashoor (مجلة بغداد للعلوم)
Since Internet Protocol version 6 is a new technology, insecure network configurations are inevitable. The researchers contributed a lot to spreading knowledge about IPv6 vulnerabilities and how to address them over the past two decades. In this study, a systematic literature review is conducted to analyze research progress in IPv6 security field following the Preferred Reporting Items for the Systematics Review and Meta-Analysis (PRISMA) method. A total of 427 studies have been reviewed from two databases, IEEE and Scopus. To fulfil the review goal, several key data elements were extracted from each study and two kinds of analysis were administered: descriptive analysis and literature classification. The results show positive signs of the research contributions in the field, and generally, they could be considered as a reference to explore the research of in the past two decades in IPv6 security field and to draw the future directions. For example, the percentage of publishing increased from 147 per decade from 2000-2010 to 330 per decade from 2011 to 2020 which means that the percentage increase was 124%. The number of citations is another key finding that reflects the great global interest in research devoted to IPv6 security issues, as it was 409 citations in the decade from 2000-2010, then increased to 1643 citations during the decade from 2011 to 2020, that is, the percentage increase was 302%.